2005
DOI: 10.1017/s0266467405002488
|View full text |Cite
|
Sign up to set email alerts
|

The impact of light quality and leaf wetness on photosynthesis in north-west Andean tropical montane cloud forest

Abstract: Photosynthesis was limited by low-intensity photosynthetically active radiation (PAR) and leaf wetness in a lower montane cloud forest (LMCF) of Cauca, Colombia. Mean PAR intensity remained below the saturation level for leaf-scale net photosynthesis (Pn) throughout the solar day during the wet season and for most of the solar day during the dry season. PAR represented a smaller fraction of total solar radiation (K↓) in LMCF than in lowland rain forest (LRF). In LMCF trees and shrubs, mean PAR-saturated Pn ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 28 publications
5
89
0
1
Order By: Relevance
“…1a) because the environmental conditions that presented during the sampling in the flowering stage and the first range measured in the fructification stage indicate that, with an increase of radiation to over 500 μmol/m 2 s, photosynthesis increases. At the same time, the mist, besides limiting the available radiation, moistened the surfaces of the leaves, decreasing the diffusion of CO 2 to the interior of the leaves (Nobel, 1999;Guy-Letts and Mulligan, 2005). In addition, when radiation decreases considerably, as registered for the fructification stage sampling, the stomatal conductance remains very low, although the C i /C a data indicated that there were no stomatal limitations in Tena.…”
Section: Discussionmentioning
confidence: 99%
“…1a) because the environmental conditions that presented during the sampling in the flowering stage and the first range measured in the fructification stage indicate that, with an increase of radiation to over 500 μmol/m 2 s, photosynthesis increases. At the same time, the mist, besides limiting the available radiation, moistened the surfaces of the leaves, decreasing the diffusion of CO 2 to the interior of the leaves (Nobel, 1999;Guy-Letts and Mulligan, 2005). In addition, when radiation decreases considerably, as registered for the fructification stage sampling, the stomatal conductance remains very low, although the C i /C a data indicated that there were no stomatal limitations in Tena.…”
Section: Discussionmentioning
confidence: 99%
“…TMCFs net primary productivity (NPP) is also low compared with lowland rainforests, and productivity decreases with increasing altitude in rates ranging between 1.0 and 6.6 Mg C ha -1 y -1 km -1 (Raich and others 1997;Kitayama and Aiba 2002;Girardin and others 2010). Explanations for the lower productivity of TMCFs include the lower levels of photosynthetic active radiation (PAR) because of frequent cloud immersion, lower average temperatures, periodic water deficiencies, leaf wetness that potentially inhibits photosynthesis, and lower nutrient supply (Bruijnzeel and Veneklaas 1998;Waide and others 1998;Letts and Mulligan 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most obvious changes is the reduction in tree size (Lieberman and others 1996;Raich and others 1997;Aiba and Kitayama 1999;Pollmann and Hildebrand 2005;Shi and others 2008), which is accompanied by a reduction in aboveground net primary production (NPP) from tropical lowland to upper montane forests (Hawaii: Raich and others 1997;Sabah, Malaysia: Kitayama and Aiba 2002;Puerto Rico: Weaver andMurphy 1990, Wang andothers 2003;Peru: Girardin and others 2010;Ecuador: Moser and others 2011;Leuschner and others, in press). One of the possible underlying causes is the temperature decrease, but N limitation of tree growth may also be involved in certain mountains where a decrease of foliar N concentration and an increase in leaf longevity with elevation was found (for example, Tanner and others 1998;Letts and Mulligan 2005;Moser and others 2010). Grubb and Tanner (1976) and Grubb (1977) identified smaller and thicker leaves with lower N concentrations as being characteristic for the trees at high elevations in tropical mountains.…”
Section: Introductionmentioning
confidence: 99%